Lithium ion battery with improved needle penetration and method of making the same
Patent Information
- Application Number
- CN202611246221.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]锂离子电池凭借其高能量密度、长循环寿命及无记忆效应等优势,已广泛应用于消费电子、电动工具、新能源汽车及储能系统等领域,其中,圆柱型锂离子电池(如18650、21700等规格)因标准化程度高、生产工艺成熟、成本可控,长期占据市场重要份额,然而,当圆柱电池在遭受尖锐物体穿刺(如钢针刺入)时,内部隔膜被刺破,正负极片直接接触从而形成局部内部短路,短路电流瞬间产生大量焦耳热,进而引发电解液分解、隔膜熔融收缩,最终导致热失控,严重时表现为起火、爆炸或冒烟等安全事故
1、本发明通过在电解液中添加质量分数为0.8%~2.0%的丙烷磺酸内酯,并配合复合隔膜、极耳垂直布置及绝缘胶带、钢壳内部绝缘套等机械结构优化措施,使电解液配方与机械结构产生显著的协同防护效应,能够在不牺牲电池能量密度和常规电化学性能的前提下,有效抑制针刺短路引发的热失控,显著提升锂离子电池的针刺通过率,达到不起火、不爆炸、不冒烟的核心安全目标,同时该方案工艺兼容性好,易于工业化生产。
Smart Images

Figure CN122992189A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a lithium-ion battery with improved needle penetration rate and its preparation method. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and no memory effect, have been widely used in consumer electronics, power tools, new energy vehicles, and energy storage systems. Among them, cylindrical lithium-ion batteries (such as 18650 and 21700 specifications) have long occupied an important market share due to their high degree of standardization, mature production process, and controllable cost. However, when a cylindrical battery is punctured by a sharp object (such as a steel needle), the internal separator is punctured, and the positive and negative electrodes come into direct contact, forming a local internal short circuit. The short circuit current instantly generates a large amount of Joule heat, which in turn causes the electrolyte to decompose and the separator to melt and shrink, ultimately leading to thermal runaway. In severe cases, this manifests as safety accidents such as fire, explosion, or smoke.
[0003] Currently, the industry's methods to improve the needle penetration safety of cylindrical lithium-ion batteries mainly focus on separator modification, electrode structure optimization, or the addition of electrolyte flame retardants. However, these methods all have certain limitations. For example, although separator modification can improve heat resistance, it cannot fundamentally suppress internal short circuits after puncture. Electrode structure optimization often comes at the cost of battery energy density. Although traditional flame retardant additives can delay combustion, they are difficult to prevent the thermal runaway process caused by puncture short circuits. Therefore, they cannot meet the core requirements of not igniting, not exploding, and not emitting smoke in the needle penetration test.
[0004] Electrolyte is the core component of lithium-ion batteries, and its thermal stability and interfacial reaction characteristics have a decisive impact on battery safety. Traditional electrolytes are highly susceptible to violent reactions under needle penetration conditions, leading to battery fires or even explosions. This is mainly due to the flammability of the electrolyte itself, as well as the extremely high temperatures and short-circuit currents generated locally during the needle penetration process. Specifically, when a steel needle pierces the battery, the interfacial reaction between the electrolyte and the positive electrode material rapidly releases a large amount of heat, significantly exacerbating the internal temperature rise of the battery. Furthermore, some electrolyte decomposes after needle penetration, generating flammable gases, further... To mitigate the risk of combustion, propane sulfonate lactone (PST), a common electrolyte additive in lithium-ion batteries, is primarily used in existing technologies to improve battery cycle life, enhance negative electrode interface stability, and suppress lithium dendrite growth. However, there are no reports to date of using PST specifically to improve the needle penetration safety of cylindrical batteries, nor has the potential synergistic protection mechanism between PST and battery mechanical structures (such as separator type, tab layout, and insulation design) been revealed. Based on this, a lithium-ion battery with improved needle penetration pass rate and its preparation method are provided, which can eliminate the drawbacks of existing methods. Summary of the Invention
[0005] The purpose of this invention is to provide a lithium-ion battery with improved needle penetration rate and its preparation method, so as to solve the problems in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A lithium-ion battery with improved needle penetration pass rate and its preparation method, comprising the following steps: Step 1: Electrolyte preparation: Cyclic carbonate and chain carbonate are mixed in a certain proportion as an organic solvent. Lithium salt is added to the organic solvent and stirred until completely dissolved. Then, propane sulfonate lactone, fluoroethylene carbonate, and lithium difluorooxalate borate are added sequentially and stirred evenly to obtain the electrolyte. The mass fraction of propane sulfonate lactone in the electrolyte is 0.8%~2.0%. Step 2: Preparation of positive electrode sheet: Mix the positive electrode active material, conductive agent and binder in proportion, add solvent to make positive electrode slurry, coat the positive electrode slurry onto aluminum foil current collector, and bake, roll and cut to form positive electrode sheet; Step 3: Preparation of negative electrode sheet: Mix the negative electrode active material, conductive agent, binder and thickener in proportion, add solvent to make negative electrode slurry, coat the negative electrode slurry onto copper foil current collector, and bake, roll and cut to form negative electrode sheet; Step 4: Separator selection: The separator is a composite separator, which is composed of a polyethylene membrane layer and a polyphenylene sulfide membrane layer. Step 5: Cell Assembly: The positive electrode sheet obtained in Step 2, the separator selected in Step 4, and the negative electrode sheet obtained in Step 3 are stacked and wound in sequence to form the main body of the cell. The main body of the cell is installed in a steel shell, and an insulating sleeve is set inside the steel shell. The positive electrode tab and the negative electrode tab are perpendicular to each other and far away from the center of the cell. The conductive sheets of the positive and negative electrode tabs are covered with insulating tape. The electrolyte prepared in Step 1 is injected into the steel shell, and the cap assembly is sealed. After formation, aging and capacity testing, a lithium-ion battery is obtained.
[0007] Based on the above technical solutions, the present invention also provides the following optional technical solutions: In one alternative: the cyclic carbonate in step one is ethylene carbonate, the chain carbonate is dimethyl carbonate and methyl ethyl carbonate, the mass ratio of ethylene carbonate, dimethyl carbonate and methyl ethyl carbonate is 2:3:5, the lithium salt is lithium hexafluorophosphate, the concentration of lithium hexafluorophosphate in the electrolyte is 1.0~1.2 mol / L, and the mass fraction of fluoroethylene carbonate in the electrolyte is 1.5%~3.0%.
[0008] In one alternative: the electrolyte in step one is further supplemented with vinylene carbonate, which is a conditioning additive.
[0009] In one alternative: triphenylphosphine, a flame retardant, is also added to the electrolyte in step one.
[0010] In one alternative: the positive electrode active material in step two is a mixture of NCM and LMFP, the conductive agent is a mixture of SP and CNTs with a mass ratio of SP to CNTs of 4:1, the binder is PVDF, the mass ratio of positive electrode active material, conductive agent and binder is 95.5%:2.5%:1.0%, the solvent is N-methylpyrrolidone, and the solid content of the positive electrode slurry is 65%.
[0011] In one alternative: the negative electrode active material in step three is graphite, the conductive agent is SP, the binder is SBR, the thickener is CMC, the mass ratio of graphite, SP, SBR and CMC is 92.5%:2.0%:1.2%:2.3%, and the solvent is deionized water.
[0012] In one alternative: the composite membrane in step four has a thickness of 11 μm, of which the polyethylene film layer has a thickness of 9 μm and the polyphenylene sulfide film layer has a thickness of 2 μm. The longitudinal heat shrinkage rate of the composite membrane is 3.5% and the transverse heat shrinkage rate is 4.5%.
[0013] In one alternative: the steel shell in step five is a standard 18650 steel shell. After the positive electrode, composite separator and negative electrode are wound to form the main body of the cell, the main body of the cell is encapsulated in the steel shell. Electrolyte is injected into the gap between the steel shell and the main body of the cell, and the cap assembly is sealed on the top of the steel shell.
[0014] A lithium-ion battery with improved needle penetration rate is prepared by the above-mentioned method.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention adds 0.8% to 2.0% propane sulfonate lactone to the electrolyte and, in conjunction with mechanical structure optimization measures such as composite separator, vertical arrangement of tabs, insulating tape, and internal insulating sleeve of steel shell, achieves a significant synergistic protective effect between the electrolyte formulation and mechanical structure. This effectively suppresses thermal runaway caused by needle penetration short circuit without sacrificing battery energy density and conventional electrochemical performance, significantly improving the needle penetration pass rate of lithium-ion batteries and achieving the core safety goals of no fire, no explosion, and no smoke. At the same time, this solution has good process compatibility and is easy to industrialize.
[0016] 2. This invention utilizes an organic solvent system, along with additives such as lithium hexafluorophosphate, PST, fluoroethylene carbonate, and lithium difluorooxalate borate, to optimize the solvation structure of lithium ions and the quality of the electrode interface film. This significantly improves ionic conductivity and interface stability, enabling the battery to retain a capacity of over 98% after 1000 cycles. Simultaneously, it effectively reduces internal resistance, ensuring a long service life.
[0017] 3. This invention utilizes a positive electrode sheet with a mixture of NCM / LMFP active materials and SP / CNTs composite conductive agents, and a negative electrode sheet with an optimized graphite / SP / SBR / CMC system. These materials work synergistically with the electrolyte formulation to significantly improve the battery's discharge performance under extreme temperatures. The capacity retention rates at 60°C and -20°C can reach over 92% and 79%, respectively, thereby broadening the battery's operating temperature range and enhancing its environmental adaptability. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the overall battery manufacturing process of the present invention.
[0019] Figure 2 This is a schematic diagram of the electrolyte preparation process of the present invention. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Example
[0021] like Figures 1-2 As shown, a lithium-ion battery with improved needle penetration rate and its preparation method include the following steps: Step 1: Electrolyte preparation Weigh ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of 2:3:5 and mix them to obtain an organic solvent. Add lithium hexafluorophosphate (LiPF6) to the mixed solvent and stir at low speed until completely dissolved. Control the concentration of LiPF6 to 1.1 mol / L. Add propane sulfonate lactone (PST), fluoroethylene carbonate (FEC), vinylene carbonate, lithium difluorooxalate borate (MMDS), and triphenylphosphine flame retardant to the system in sequence, wherein the mass fraction of PST is 1.2% and the mass fraction of FEC is 2.0%. After all additives are added, stir at low speed for 30 min, let stand to remove bubbles, and control the water content of the electrolyte to ≤20 ppm and the acidity to ≤50 ppm to obtain the finished electrolyte. Step 2: Preparation of the positive electrode sheet NCM and LMFP mixed positive electrode active material, SP / CNTs composite conductive agent (SP to CNTs mass ratio 4:1), and PVDF binder were added to a stirred tank at a mass ratio of 95.5%:2.5%:1.0%. N-methylpyrrolidone was added as a solvent, and the mixture was stirred at high speed to prepare a positive electrode slurry with a solid content of 65%. The slurry was uniformly coated on the surface of aluminum foil current collector, baked at a constant temperature of 110℃ to remove the solvent, and then compacted by roller pressing and cut into strips to obtain standard positive electrode sheets. Step 3: Preparation of negative electrode sheet Graphite anode active material, SP conductive agent, SBR binder and CMC thickener are mixed in a mass ratio of 92.5%:2.0%:1.2%:2.3%, and deionized water is added and stirred at high speed to prepare anode slurry. The anode slurry is coated on copper foil current collector, dried at 100°C, rolled and cut into sheets to complete the preparation of anode sheet. Step 4: Diaphragm Selection A composite membrane with a total thickness of 11 μm was selected, with an inner polyethylene (PE) film thickness of 9 μm and an outer polyphenylene sulfide (PPS) film thickness of 2 μm. The longitudinal heat shrinkage rate of this composite membrane is 3.5%, and the transverse heat shrinkage rate is 4.5%. Step 5: Cell Assembly The positive electrode sheet, composite separator, and negative electrode sheet are stacked and wound to form the main body of the battery cell. The battery cell is then installed in a standard 18650 steel shell, with an insulating sleeve installed inside the steel shell. The positive and negative electrode tabs are arranged vertically and away from the center of the battery cell. Insulating tape is attached to the conductive sheets of the positive and negative electrode tabs. The electrolyte prepared in step one is injected into the gap between the steel shell and the battery cell. The cap assembly is then assembled and sealed. The battery cell undergoes formation, high-temperature aging, and capacity testing processes to obtain the finished high-safety cylindrical lithium-ion battery. Example
[0022] A lithium-ion battery with improved needle penetration pass rate and its preparation method, comprising the following steps: The overall process steps are consistent with those in Example 1, except that the mass fraction of propane sulfonate lactone (PST) in the electrolyte is adjusted to 0.8%, the mass fraction of fluoroethylene carbonate (FEC) is adjusted to 1.5%, and the concentration of lithium hexafluorophosphate (LiPF6) is adjusted to 1.0 mol / L. The remaining raw material ratios, process parameters, separator specifications, and cell assembly structure are exactly the same as in Example 1. Example
[0023] A lithium-ion battery with improved needle penetration pass rate and its preparation method, comprising the following steps: The overall process steps are consistent with those in Example 1, except that the mass fraction of propane sulfonate lactone (PST) in the electrolyte is adjusted to 2.0%, the mass fraction of fluoroethylene carbonate (FEC) is adjusted to 3.0%, and the concentration of lithium hexafluorophosphate (LiPF6) is adjusted to 1.2 mol / L. The remaining raw material ratios, process parameters, separator specifications, and cell assembly structure are exactly the same as in Example 1.
[0024] Comparative Example 1 The overall process steps are consistent with those in Example 1, except that propane sulfonate lactone (PST) is not added to the electrolyte formulation, and only equal amounts of FEC, vinylene carbonate, lithium difluorooxalate borate, and triphenylphosphine are retained. The LiPF6 concentration is maintained at 1.1 mol / L, and the electrode, separator, and cell assembly structures are all the same as in Example 1, thus preparing a conventional 18650 battery without PST-modified electrolyte.
[0025] Comparative Example 2 The overall process steps are consistent with those of Example 1, except that: the electrolyte formula is completely the same as that of Example 1 (PST 1.2%, FEC 2.0%, LiPF6 1.1mol / L), all mechanical structure optimization designs are cancelled, the diaphragm is replaced with a 12μm ordinary single-layer PE diaphragm with a longitudinal heat shrinkage rate of 6.0% and a transverse heat shrinkage rate of 7.5%, the positive and negative electrode tabs are arranged in parallel, the conductive sheets of the electrode tabs are not pasted with insulating tape, and no insulating sleeve is added inside the steel shell. The preparation processes of the other electrode sheets and electrolytes remain unchanged.
[0026] Comparative Example 3 The overall process steps are consistent with those in Example 1, except that propane sulfonate lactone (PST) is removed from the electrolyte, and only 2.0% FEC, lithium difluorooxalate borate, vinylene carbonate, and triphenylphosphine are added. The optimization schemes for all mechanical structures, such as the diaphragm, tab insulation, and steel shell insulation sleeve, are completely consistent with those in Example 1.
[0027] Experimental Example Rated capacity (mAh) 2050 2020 2030 2040 2045 2040 Internal resistance (mΩ) 13 14 13 16 15 14 Capacity retention rate after 1000 cycles (%) 98 97 90 86 88 90 Needle prick test (GB43854-2024) OK (5 / 5) OK (5 / 5) NG (4 / 5) NG (3 / 5) NG (3 / 5) NG (2 / 5) Discharge capacity retention rate at 60℃ (%) 92 91 85 80 82 84 -20℃ discharge capacity retention rate (%) 79 73 70 72 68 70 The above test results show that the cylindrical lithium-ion batteries of Examples 1-2 of the present invention can all pass the nail penetration test (5 / 5) smoothly, and their electrochemical performance is better than that of the comparative examples. This proves that the technical solution of the present invention can significantly improve the nail penetration safety of the battery and ensure the normal use performance of the battery. Comparing Example 1 with Comparative Examples 2 and 3, it can be seen that: Comparative Example 2 only contains PST electrolyte optimization but no mechanical structure optimization, and the nail penetration pass rate is 3 / 5; Comparative Example 3 only contains mechanical structure optimization but does not contain PST in the electrolyte, and the nail penetration pass rate is only 2 / 5; while Example 1 combines the PST-containing electrolyte formulation with mechanical structure optimization such as composite separator, tab insulation design, and steel shell insulation sleeve, and the nail penetration pass rate reaches 5 / 5. The above results fully demonstrate that there is a significant synergistic effect between the electrolyte formulation and the mechanical structure. Both are indispensable and work together to ensure the safety of the battery under nail penetration conditions.
[0028] The above description is merely a specific embodiment of this disclosure, but the scope of protection of this disclosure is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this disclosure should be included within the scope of protection of this disclosure. Therefore, the scope of protection of this disclosure should be determined by the scope of the claims.
Claims
1. A lithium-ion battery with improved needle penetration rate and its preparation method, characterized in that, Includes the following steps: Step 1: Electrolyte preparation: Cyclic carbonate and chain carbonate are mixed in a certain proportion as an organic solvent. Lithium salt is added to the organic solvent and stirred until completely dissolved. Then, propane sulfonate lactone, fluoroethylene carbonate, and lithium difluorooxalate borate are added sequentially and stirred evenly to obtain the electrolyte. The mass fraction of propane sulfonate lactone in the electrolyte is 0.8%~2.0%. Step 2: Preparation of positive electrode sheet: Mix the positive electrode active material, conductive agent and binder in proportion, add solvent to make positive electrode slurry, coat the positive electrode slurry onto aluminum foil current collector, and bake, roll and cut to form positive electrode sheet; Step 3: Preparation of negative electrode sheet: Mix the negative electrode active material, conductive agent, binder and thickener in proportion, add solvent to make negative electrode slurry, coat the negative electrode slurry onto copper foil current collector, and bake, roll and cut to form negative electrode sheet; Step 4: Separator selection: The separator is a composite separator, which is composed of a polyethylene membrane layer and a polyphenylene sulfide membrane layer. Step 5: Cell Assembly: The positive electrode sheet obtained in Step 2, the separator selected in Step 4, and the negative electrode sheet obtained in Step 3 are stacked and wound in sequence to form the main body of the cell. The main body of the cell is installed in a steel shell, and an insulating sleeve is set inside the steel shell. The positive electrode tab and the negative electrode tab are perpendicular to each other and far away from the center of the cell. The conductive sheets of the positive and negative electrode tabs are covered with insulating tape. The electrolyte prepared in Step 1 is injected into the steel shell, and the cap assembly is sealed. After formation, aging and capacity testing, a lithium-ion battery is obtained.
2. The lithium-ion battery and its preparation method for improving needle penetration rate according to claim 1, characterized in that, In step one, the cyclic carbonate is ethylene carbonate, the chain carbonate is dimethyl carbonate and methyl ethyl carbonate, the mass ratio of ethylene carbonate, dimethyl carbonate and methyl ethyl carbonate is 2:3:5, the lithium salt is lithium hexafluorophosphate, the concentration of lithium hexafluorophosphate in the electrolyte is 1.0~1.2 mol / L, and the mass fraction of fluoroethylene carbonate in the electrolyte is 1.5%~3.0%.
3. The lithium-ion battery and its preparation method for improving needle penetration rate according to claim 1, characterized in that, In step one, the electrolyte also contains vinylene carbonate, which is a conditioning additive.
4. The lithium-ion battery and its preparation method for improving needle penetration rate according to claim 1, characterized in that, Triphenylphosphine, a flame retardant, is also added to the electrolyte in step one.
5. A lithium-ion battery with improved needle penetration rate and its preparation method according to claim 1, characterized in that, In step two, the positive electrode active material is a mixture of NCM and LMFP, the conductive agent is a mixture of SP and CNTs with a mass ratio of SP to CNTs of 4:1, the binder is PVDF, the mass ratio of positive electrode active material, conductive agent and binder is 95.5%:2.5%:1.0%, the solvent is N-methylpyrrolidone, and the solid content of the positive electrode slurry is 65%.
6. A lithium-ion battery with improved needle penetration rate and its preparation method according to claim 1, characterized in that, In step three, the negative electrode active material is graphite, the conductive agent is SP, the binder is SBR, the thickener is CMC, and the mass ratio of graphite, SP, SBR and CMC is 92.5%:2.0%:1.2%:2.3%. The solvent is deionized water.
7. A lithium-ion battery with improved needle penetration rate and its preparation method according to claim 1, characterized in that, The composite membrane in step four has a thickness of 11 μm, of which the polyethylene film layer has a thickness of 9 μm and the polyphenylene sulfide film layer has a thickness of 2 μm. The longitudinal heat shrinkage rate of the composite membrane is 3.5% and the transverse heat shrinkage rate is 4.5%.
8. A lithium-ion battery with improved needle penetration rate and its preparation method according to claim 1, characterized in that, In step five, the steel shell is a standard 18650 steel shell. After the positive electrode, composite separator and negative electrode are wound to form the main body of the cell, the main body of the cell is encapsulated in the steel shell. Electrolyte is injected into the gap between the steel shell and the main body of the cell, and the cap assembly is sealed on the top of the steel shell.
9. A lithium-ion battery with improved needle penetration pass rate, characterized in that, Prepared by the method described in any one of claims 1-8.